2050. Plasma Next-Generation Sequencing for Pathogen Detection in Pediatric Patients at Risk for Invasive Fungal Infection. (26th November 2018) - Armstrong, Amy; Rossoff, Jenna; Aquino, Romielle; Hollemon, Desiree; Hong, David; Chaudhury, Sonali; Muller, William
Abstract: Background: Invasive fungal infection (IFI) is a major cause of mortality and morbidity among immunocompromised patients. Microbiologic culture of biopsy samples remains the diagnostic gold standard. Noninvasive biomarker testing can provide clinically useful information, but does not give species-level identification. Next-generation sequencing (NGS) of cell-free plasma is a noninvasive approach for species-level identification of pathogens, and may guide specific treatment. We sought to describe the diagnostic utility of plasma NGS in high-risk immunocompromised pediatric patients, correlating results with standard microbiology studies. Methods: Plasma from at-risk immunocompromised patients with suspected IFI was tested using cell-free plasma NGS (Karius, Redwood City, CA). Human reads were removed, and remaining sequences aligned to a curated database including >1, 000 pathogens. Organisms present above a predefined significance threshold were reported. Results: Forty evaluable patients were enrolled, the majority of whom had underlying oncologic diagnoses. Risk for IFI included prolonged febrile neutropenia (FN) in 22 patients, recrudescent FN in 7, concern for IFI on imaging in 8, and concern for IFI based solely on other clinical findings in 3. Six patients met established criteria for proven IFI, 1 for probable IFI, and 13 for possible IFI. NGS plasma testing identified a pathogen which was cultured from infected tissue or blood in 4 of 6 proven cases; one patient with localized cutaneous Rhizopus had negative NGS results. A patient with probable IFI (positive β-D-glucan) had P. jirovecii identified by NGS. Among 33 patients without proven or probable IFI, NGS testing identified a fungus in one ( C. glabrata ), no organism in 11, and potential alternative sources of fever in 16. Conclusion: Plasma NGS testing can detect IFI from blood. The test identified fungi from proven IFI, and detected other pathogens in both probable and possible IFI cases. Many patients at risk received prolonged courses of antifungals despite negative testing, suggesting a possible future role for NGS testing in ruling out IFI. Future studies should more definitively evaluate the positive and negative predictive value for NGS testing in patients at risk of IFI. Disclosures: R. Aquino, Karius, Inc.: Employee, Salary. D. Hollemon, Karius: Employee, Salary. D. Hong, Karius, Inc.: Employee, Salary.